The Role and Dynamics of Actor Relations in Implementing Defense Industry-Based Policies: A Comparative Study of Indonesia and Brazil - Achmadi, Budhi; Sutawidjaya, Ahmad Hidayat (Journal of Ecohumanism, 2024)
This study explores the role and dynamics of actor relations in implementing defense industry-based policies through a comparative analysis of Indonesia and Brazil. The aim is to understand how key actors—government bodies, military institutions, state-owned enterprises, private companies, and international partners—affect policy execution and defense industry outcomes in both countries. Employing qualitative research methods with secondary data sources, the study examines the contributions and interactions of these actors as detailed in the provided table. The findings reveal that Indonesia relies heavily on state control and international partnerships for technology transfer, while Brazil integrates private sector innovation and diverse international collaborations. Key differences include Indonesia’s centralized approach versus Brazil’s market-oriented model, with implications for policy alignment and capability development. The conclusions emphasize the importance of effective communication and stakeholder alignment to address challenges such as misalignment between military needs and industrial capabilities. Recommendations for both countries include enhancing collaboration and technology transfer, managing internal conflicts, and optimizing resource allocation.